Transcriptome-based identification and validation of reference genes for plant-bacteria interaction studies using Nicotiana benthamiana - Pombo, Marina Alejandra (2019)
RT-qPCR is a widely used technique for the analysis of gene expression. Accurate estimation of transcript abundance relies strongly on a normalization that requires the use of reference genes that are stably expressed in the conditions analyzed. Initially, they were adopted from those used in Northern blot experiments, but an increasing number of publications highlight the need to fnd and validate alternative reference genes for the particular system under study. The development of high-throughput sequencing techniques has facilitated the identifcation of such stably expressed genes. Nicotiana benthamiana has been extensively used as a model in the plant research feld. In spite of this, there is scarce information regarding suitable RT-qPCR reference genes for this species. Employing RNA-seq data previously generated from tomato plants, combined with newly generated data from N. benthamiana leaves infltrated with Pseudomonas fuorescens, we identifed and tested a set of 9 candidate reference genes. Using three diferent algorithms, we found that NbUbe35, NbNQO and NbErpA exhibit less variable gene expression in our pathosystem than previously used genes. Furthermore, the combined use of the frst two is sufcient for robust gene expression analysis. We encourage employing these novel reference genes in future RT-qPCR experiments involving N. benthamiana and Pseudomonas spp.